Analisis Implementasi Program Kelas Ibu Hamil Dengan Inovasi Pemberian Madu Kurma Untuk Penanganan Anemia Di TPMB Veronika Sinaga - Fitriani; Ridni Husnah; Afizah Ratu Amaryllis (Akademi Keperawatan Yarsi Samarinda, 2026)
Anemia among pregnant women is a significant global and regional health issue; Batam City has recorded a prevalence of 37%, driven by low adherence to consumption and suboptimal iron absorption from Blood-Supplementing Tablet (TTD) supplementation. This study aimed to analyze the implementation of a